2018
DOI: 10.1186/s12877-018-0965-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical interventions on physical performance and physical activity in older patients during hospitalization: a systematic review

Abstract: BackgroundTo counteract decline in physical performance and physical activity in older patients during hospitalization, multiple physical interventions were developed. However, it is unknown whether these are effective in this particular population. This systematic review aimed to identify the effect of physical interventions on physical performance and physical activity in older patients during hospitalization.MethodsThe systematic search included PubMed, EMBASE, Cinahl, the Trials database of The Cochrane Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…The effect of early physical exercise interventions in acutely hospitalized older patients has already been examined in a number of previous systematic reviews [3, 813], reporting heterogeneous results across different outcomes and outcome categories such as hospital outcomes, adverse clinical events, or functional and mobility outcomes. A potential cause of this inconclusive evidence for the benefits of early physical exercise interventions has been addressed in one of these reviews, hypothesizing that the adaption level of the intervention to the capabilities of the patients might have played a critical role for the effectiveness of such interventions in acutely hospitalized older patients [13]. However, contrary to this hypothesis, patient-tailored physical exercise interventions were not found to be superior to those interventions that were not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of early physical exercise interventions in acutely hospitalized older patients has already been examined in a number of previous systematic reviews [3, 813], reporting heterogeneous results across different outcomes and outcome categories such as hospital outcomes, adverse clinical events, or functional and mobility outcomes. A potential cause of this inconclusive evidence for the benefits of early physical exercise interventions has been addressed in one of these reviews, hypothesizing that the adaption level of the intervention to the capabilities of the patients might have played a critical role for the effectiveness of such interventions in acutely hospitalized older patients [13]. However, contrary to this hypothesis, patient-tailored physical exercise interventions were not found to be superior to those interventions that were not.…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary to this hypothesis, patient-tailored physical exercise interventions were not found to be superior to those interventions that were not. Another potential cause for the still limited evidence might be the use of various outcome measures, which has been reported in most of the aforementioned reviews [3, 10, 11, 13]. However, none of these reviews specifically addressed the heterogeneity and the appropriateness of the outcome measures selected in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The results from our study are difficult to compare with other studies on physical activity interventions during hospitalization, 8 , 24 27 because these did not investigate multicomponent interventions including various eHealth elements/non-eHealth elements at the same time. However, studies that specifically evaluated the feasibility of single eHealth interventions, such as the study by Laver et al 19 on an interactive gaming program, showed that their use in a hospital setting was feasible.…”
Section: Discussionmentioning
confidence: 69%
“…A recent systematic review, concluding that the effect of physical activity interventions on physical performance in older patients during hospitalization was uncertain, included 15 trials. 8 The interventions used in those trials varied considerably and comprised (supervised) physical exercise program(s) with mobility, flexibility, strength, balance, walking and functional exercises, [9][10][11][12][13][14][15][16][17][18][19] proprioceptive neuromuscular facilitation, 20 electrical stimulation, 21 vibration training 22 and horse riding stimulation. 23 Four RCTs published afterwards [24][25][26][27] investigated one or more (supervised) physical exercise program(s) including mobility, flexibility, strength, balance, walking and functional exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple interventions targeting physical activity promotion in older hospitalized patients have been developed, but the results of such interventions were inconsistent (Scheerman, Raaijmakers, Otten, Meskers, & Maier, 2018). Implementation of interventions in clinical practice is challenging since it is affected by factors on organizational, professional, intervention and patient level (Chaudoir, Dugan, & Barr, 2013).…”
Section: Introductionmentioning
confidence: 99%